Prediction of land use/land cover change in Indonesia using the open source land cover dataset: a review - Astuty, Yulia Indri; Dimyati, Muhammad (Geodesy and Cartography, 2024)
Indonesia, as a promising developing country, faced with the fact that the development is not evenly distributed. Moreover, the number of people living in urban area is more and increasing at least 2.1% per year according to Central Statistics Agency (BPS). Hence, urban area has better transportation access and public facilites. However, high number of people living in urban area leads to spatial confilcts if spatial planning is not carried out based on sustainable development. For this reason, it is necessary to carry out long-term spatial planning using predictions of changes in land use/land cover in Indonesia. The purpose of this literature review is to get an overview of research development trends related to predictions of land use/land cover in Indonesia. Based on bibliometric analysis, the research trend related to this topic is that most research locations are in urban areas using satellite imagery input data and the Cellular Automata-Marcov Chain (CA-MC) method for making predictive models. Meanwhile, open source land cover datasets have not been widely used in land use/land cover prediction research in Indonesia. This can be used as input for updating further research.